In silico improvement of affinity for highly protective anti-malarial antibodies - Mateo Reveiz; Prabhanshu Tripathi; Lais Da Silva Pereira; Patience Kerubo Kiyuka; Tracy Liu; Yongping Yang; Baoshan Zhang; Dorra Benmohamed; Brian G. Bonilla; Carl W. Carruthers, Jr.; Marlon Dillon; Daniel Gowetski; et al. (iScience)
Summary: The monoclonal antibody CIS43 preferentially binds the junctional region of Plasmodium falciparum circumsporozoite protein (PfCSP) and is highly protective in humans. Here, we develop an in silico pipeline to improve antigen-antibody interaction energies and apply it to CIS43 variants elicited in CIS43-germline knock-in mice. Improved binding of CIS43 variants to the CIS43 junctional epitope (PfCSP peptide 21) was achieved by introducing single and double amino acid substitutions in the peptide 21-proximal heavy- and light-chain-variable regions. The best in silico designed variant, antibody P3-43-LS, was 2- to 3-fold more protective than antibody CIS43-LS, the clinical version of CIS43 with half-life extending leucine-serine (LS) mutations, and had comparable protection to the current best-in-class antibody (iGL-CIS43.D3-LS) to this region. Crystal structures of the improved antibodies revealed atomic-level interactions accounting for gains in binding affinity. This in silico approach to improve antibody affinity can thus be used to enhance potency of PfCSP monoclonal antibodies.